AB0250 Wrist Ultrasound Better Correlates with Disease Activity Score (DAS28) in Rheumatoid Arthritis Patients Treated with Biologics. (9th June 2015) - Opris, D.; Borangiu, A.; Gudu, T.; Saulescu, I.; Groseanu, L.; Predeteanu, D.; Ionescu, R.
Abstract : Objectives: To assess which particular joint ultrasound (US) evaluation better correlate with disease activity based on DAS28 in rheumatoid arthritis (RA) patients treated with biologics. Methods: Consecutive RA patients on stable biologic treatment for more than 6 months were evaluated. Clinical and US evaluation were performed by two independent assessors, the same day as all laboratory tests. The scanning technique and the settings of the machine (ESAOTE MY LAB70, 15 MHz linear probe) were the same for all the patients. Examinations were perform by a trained ultrasonografer who was blinded to all clinical evaluations. US of both hands (dorsal wrist, 2nd to 5th volar metacarpophalangeal and 2nd to 4th volar proximal interphalangeal) was done. Synovial hypertrophy and power Doppler (PD) signal were scored (grade 0–3). Synovial hypertrophy >2 plus power Doppler signal was classified as active synovitis. Based on DAS284v(ESR) patients were split in 2 groups: remission and non-remission. Results: One hundred and six patients were evaluated. Most of them (84%) were females, mean age group 58.72 (11.49) years, mean disease duration 13.48 (7.4) years. Regarding the treatment, 87.7% had a DMARD associated to the biologic: 49.1% (52) patients were treated with rituximab, 27.35% (29) with etanercept, 19.9% (19) with adalimumab, 9.33% (9) with infliximab. Mean DAS28 ESR was 3.14, with 36.8% of patients being on remission. We found a significant statistical difference (p=0.005) between active synovitis score in active disease patients (82.05% of them heaving active synovitis) versus 56.41% synovitis in remission patients. Statistical significance was also found regarding inflammation markers, PD joint number, PD total score, but not regarding Grey Scale (GS) number and total score (see table ). When every joint was evaluated separately, statistically significance was found only between wrists and PD: right wrist (p=0.01) and left wrist (p=0.002), but not for GS (p=0.181 and 0.337). Conclusions: Active synovitis score, total PD joint number and total PD score correlates with DAS284vESR in rheumatoid arthritis patients treated with biologics. Both wrist US evaluation seems to be the most accurate in identifiing disease activity. Acknowledgements: This paper is partially supported by the Sectoral Operational Program Human Resources Development, financed from the European Social Found POSDRU/159/1.5/S/137390. Disclosure of Interest: None declared